2019
DOI: 10.3390/ijms20153645
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Polyunsaturated Fatty Acids on Inflammatory Markers in Patients Undergoing Dialysis: A Systematic Review with Network Meta-Analysis of Randomized Clinical Trials

Abstract: The effects of polyunsaturated fatty acids (PUFAs) on inflammatory markers among patients receiving dialysis have been discussed for a long time, but previous syntheses made controversial conclusion because of highly conceptual heterogeneity in their synthesis. Thus, to further understanding of this topic, we comprehensively gathered relevant randomized clinical trials (RCTs) before April 2019, and two authors independently extracted data of C-reactive protein (CRP), high-sensitivity C-reactive protein (hs-CRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…This Special Issue covers research articles that investigated the molecular mechanisms of inflammation [1][2][3] and injury [4,5] during different renal pathologies and renal regeneration [6], diagnostics using new biomarkers [7][8][9], and the effects of different stimuli like medication or bacterial components on isolated renal cells or in vivo models [10][11][12], all of which were summarized in a very simplified manner. Furthermore, this Special Issue contains important reviews that dealt with the current knowledge of cell death and regeneration [13,14], inflammation [15][16][17][18], and the molecular mechanisms of kidney diseases [19][20][21][22]. In addition, the potential of cell-based therapy approaches that use mesenchymal stromal/stem cells (MSCs) or their derivates is summarized [23][24][25].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This Special Issue covers research articles that investigated the molecular mechanisms of inflammation [1][2][3] and injury [4,5] during different renal pathologies and renal regeneration [6], diagnostics using new biomarkers [7][8][9], and the effects of different stimuli like medication or bacterial components on isolated renal cells or in vivo models [10][11][12], all of which were summarized in a very simplified manner. Furthermore, this Special Issue contains important reviews that dealt with the current knowledge of cell death and regeneration [13,14], inflammation [15][16][17][18], and the molecular mechanisms of kidney diseases [19][20][21][22]. In addition, the potential of cell-based therapy approaches that use mesenchymal stromal/stem cells (MSCs) or their derivates is summarized [23][24][25].…”
mentioning
confidence: 99%
“…MSCs predominantly act through secreted factors, including microRNAs that are contained within extracellular vesicles, cytoprotective effects anti-inflammatory effects, anti-apoptotic effects, and the suppression of oxidative stress. In addition, further reviews summarized the inflammation-mediated mechanisms or the inflammasome in various renal diseases [15][16][17][18]26,27]. Very interesting and new approaches shed a light on the role of non-coding RNAs, either in the progression of glomerular or tubulointerstitial kidney diseases [20] or as new therapeutic targets or biomarkers for fibrotic changes [29].…”
mentioning
confidence: 99%
“…In line with our results, Saglimbene et al in 2020 [ 37 ] demonstrated that omega-3 FAs intake might decrease cardiovascular mortality in hemodialysis patients, but it is uncertain whether omega-3 FAs intake reduces the risk of mortality or ESKD in subjects with CKD. Wu et al [ 38 ] also indicated that omega-3 FAs supplementation might improve inflammatory factors in dialysis patients. In previous systematic reviews, omega-3 FAs intake has beneficial effects on the Lipid profile of CKD patients [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, clarifying such interventions improves the quality of the pooled results and provides a better understanding of PUFA effects in dialysis patients. [40] In our experience, different regimens should also be evaluated more precisely. For instance, Vitamin E, a fat-soluble antioxidant, was frequently used either in control group or placebo group in many studies.…”
Section: Introductionmentioning
confidence: 99%